OPTIMASI WAKTU SIKLUS PRODUKSI KEMASAN PRODUK 50 ML PADA PROSES BLOW MOULDING DENGAN METODE RESPON PERMUKAAN - M. Kahlil Gibran; F.X. Kristianta (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
50 ml bottle is being processed by blow molding. There are many parameters that influence cycle time during production; This study aims to determine the influence of process variables, ie blowing time, blowing pressure and stop time of the response variable, namely the cycle time, the net and volume. In addition, to get the value for the optimization of the production cycle time 50 ml bottle while maintaining the value of quality in the bottle, ie the net value and volume. Each parameter is determined three chosen level. Middle level is taken from standard setting of machining which is being used by industry. Top and bottom level is randomized. Three stopping time are 0.5, 1.0, and 1.5 second. Blowing time are 8, 9 and 10 second. Where as, blowing pressures 5, 5.75 and 6.5 bar. Combination of among levels is based on Box Behnken design. Those three parameters are called variable process. In the other hand, variable responses are cycle time, netto and volume. Each combination is replicated 3 times and then averaged. The data then is processed by using Minitab version 16th. Square regression of the model for cycle time is ŶCT = 13,5300 – 0,0412 X1 + 0,8000 X2 + 0,1812 X3 + 0,0238 X12 – 0,2087 X22 –0,0412 X32 – 0,1150 X1 X2 – 0,0175 X1 X3 + 0,0350 X2 X3. Where X1 is blowing pressure, X2 is blowing time and X3 is stop time.The model developed then tested by residual assumption. Second stage of model testing lack of fit test. Optimization of both values, cycle time, netto and volume are searched by Response Surface Method. By the method it is found that the optimum condition of cycle time is 12.60 seconds, netto is 13.34 grams, volume is 89.87 ml The optimum condition is achieved when stop time is 1.5 second, blowing time 8 second and blowing pressure 5.34254 bars.